Selection and perception of methotrexate treatment information in people with rheumatoid arthritis. (14th June 2020) - Leonardo, Nieves; Lester, Susan; Graham, Michelle; Barrett, Claire; Whittle, Samuel; Rowett, Debra; Buchbinder, Rachelle; Hill, Catherine L.
Abstract: Objective: To determine beliefs about methotrexate (MTX) in patients with rheumatoid arthritis (RA) in relation to utilized information sources. Methods: RA patients, who were current participants in the Australian national biologic registry, completed an online questionnaire regarding their use and views about MTX (N = 1010). Participants who used MTX were asked about which MTX information sources they consulted, and whether positive or negative views were obtained. The Beliefs about Medicine Questionnaire (BMQ), was used to measure patient beliefs about MTX. Results: The survey response rate was 804/1010 (80%). MTX survey data were analyzed for 742 RA participants (mean age 59 years, 76% female, mean disease duration 19 years) who had used MTX, with 494/742 (67%) reporting current use. Participants consulted multiple information sources (median 3, interquartile range 1‐5). Rheumatologists (98%), general practitioners (GPs) (55%), internet searches (39%), educational websites (38%), and pharmacists (37%) were the most common information sources utilized. Positive MTX information was most often obtained from rheumatologists (92%), GPs (66%), and educational websites (56%). Negative information was most often obtained from relatives, social media, internet chat rooms and friends. Information from rheumatologists was the most influential on favorable BMQ MTX‐specific scores, whereas information from educational websites also affirmed the need for MTX. Conclusion: RA patients have significant concerns regarding MTX and consult a variety of sources for MTX information. However, the patient perception of this information varies widely. Rheumatologists and educational websites are the most important information sources in terms of a positive influence on the patient's perception of MTX.